Framing and Misperceptions in a Public Good Experiment - Toke R. Fosgaard; Lars Gårn Hansen; Erik Wengström (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
Earlier studies have found that a substantial part of the contributions in public good games can be explained by subjects misperceiving the game's incentives. Using a large-scale public good experiment, we show that subtle changes in how the game is framed substantially affect such misperceptions and that this explains major parts of framing effect on subjects' behavior. When controlling for the different levels of misperception between frames, the framing effect on subjects' cooperation preferences disappears.
Keywords: H41; C90; D03; 330; Public goods; Cooperation; Misperception; Framing effects; Internet experiment